E- Advertising : Theory and Practice - Singhal, Rahul (Journal of Commerce and Trade, 2008)
Today we are living in Internet era. Internet make everything very easy for the public. We can get information about anything from internet. Seeing the use of internet companies have begun to do advertising of internet. By internet companies give information about their product and service to the customers . E-advertisement is also economical for the companies. IT is a powerful tool to acquiring new customers. E-advertisement is one of the most effective ways to interact with customers. US internet advertisement spend total $ 16.9 Billion in 2006.